How is new technology changing job design? - Michael Gibbs; Sergei Bazylik (IZA World of Labor, 2022)
The IT revolution has had dramatic effects on jobs and the labor market. Many routine manual and cognitive tasks have been automated, replacing workers. By contrast, new technologies complement and create new non-routine cognitive and social tasks, making work in such tasks more productive, and creating new jobs. This has polarized labor markets: while low-skill jobs stagnated, there are fewer and lower-paid jobs for middle-skill workers, and higher pay for high-skill workers, increasing wage inequality. Advances in AI may accelerate computers' ability to perform cognitive tasks, heightening concerns about future automation of even high-skill jobs.
Keywords: J01; J23; J31; O14; 330; job design; technology; artificial intelligence; cognitive tasks; labor market polarization